Performance and Potential Study of 10kW Wind Turbine Generator for 6 Cities in Malaysia - Mustaqimah Mustaqimah (Rona Teknik Pertanian, 2013)
ABSTRACT. This study presents an analysis of the optimization by using HOMER software and financial viability of 10 kW wind turbine generator (WTG) through grid connected system for six different locations in Malaysia (Mersing, Kuching, K.Trengganu, Kudat, Melaka and Labuan). Assessment criteria comprised Total Net Present Cost (TNPC), and Cost of Energy ( COE ). The HOMER ( National Renewable Energy laboratory, US) was utilized as the assessment tool with modeling performed with hourly load data input from six cities in Malaysia. The results demonstrate that WTG has the potential to supply significant power for small scale load in conjunction with the grid-electricity supply. Optimization modeling demonstrated that the TNPC for grid connected configuration is Mersing for the lowest TNPC among the other cities which is TNPC recorded at $ -28,436 and initial cost is about $ 20,000. This mean wind grid system in Mersing is very benefit be built and reduction in greenhouse gas emission of 9,452 kg/yr. Optimization modeling also showed that Mersing is the only one among other city had showed a high potential of WTG which produced energy at 85,326 kWh/yr and purchase grid only at 4,082 kWh/year.Kajian Kinerja dan Potensi Generator Turbin Angin 10kW untuk 6 kota di MalaysiaABSTRAK. Penelitian ini menyajikan analisis optimasi dengan menggunakan software HOMER dan kesesuaian biaya untuk generator turbin angin (wind turbine generator=WTG) 10 kW sistem grid untuk enam lokasi yang berbeda di Malaysia (Mersing, Kuching, K.Trengganu, Kudat, Melaka dan Labuan). Kriteria penilaian terdiri Total Net Present Cost (TNPC) dan Cost of Energy (COE). software HOMER (National Renewable Energy laboratory, US) digunakan sebagai pemodelan dengan memasukkan data beban daya per jam dari enam kota tersebut. Hasil penelitian menunjukkan bahwa generator turbin angin (WTG) memiliki potensi untuk memasok daya yang signifikan untuk beban kecil dalam hubungannya dengan pasokan grid listrik. Optimasi Pemodelan menunjukkan bahwa Mersing memiliki TNPC terendah dibangdingkan kota lain ($ -28,436) dan initial cost sebesar $ 20,000. Hal ini bermakna bahwa Mersing memiliki potensi untuk dibangun generator turbin angin (WTG) dan pengurangan emisi gas rumah kaca 9.452 kg/tahun. Model optimasi juga menunjukkan bahwa Mersing adalah kota yang memiliki potensi besar untuk membuat sistem generator turbin angin (WTG) yang menghasilkan energi 85.326 kWjam/tahun dan pembelian daya pada jaringan grid hanya 4.082 kWjam/tahun.